Bibliometric analysis of medical related peruvian printings published during peruvian viceroyalty (XVI-XIX centuries) - Saravia, Roy (2002)
Objective: To quantify bibliometric indicators of medical printed matter published during Peruvian Viceroyalty (1585-1821). Design: Retrospective, longitudinal, descriptive study. Material and methods: In 550 printings the following indicators were studied: title, year of publication, author, document gender, thematic area, author’s nationality and profession, printing shop or printer. Results: There were 550 printings between 1585-1821, 280 (51%) published mainly between years 1780-1799. From 121 authors Hipolito Unanue was the most fruitful author with 72 (13,1%) publications. From 32 thematic areas, climatology was the most recurrent with 110 (20%) printings. The document gender mostly used was the book with 192 (34,9%) publications. Doctors had the largest concentration of publications with 243 (44,2%) printings. Most printings were published in Spanish, 513 (93,3%), and 227 (41,3%) by Peruvian authors. Conclusions: The Mercurio Peruano was quantitatively the most published medical literature during Peruvian Viceroyalty. Hipolito Unanue was the most fruitful author, and climatology the matter of most interest in the Viceroyalty medical community.